Intervensi Terapi Komplementer Nyeri Dismenore Pada Remaja Putri Menggunakan VOSviewer - Indria, Gita Ayu (STIKes Medistra Indonesia, 2024)
Complementary therapy to overcome dysmenorrhea pain in adolescents is one of the alternatives to health services, especially adolescent health. Dysmenorrhea pain experienced by adolescents during the menstrual period can interfere with adolescent activities and increase the number of adolescent pain which will affect the health of adolescents. The researcher aims to find out the bibliometric analysis in the study of the use of complementary therapy to manage dysmenorrhea pain in adolescent girls. Data collection using the Harzing's Publish or Peris application with the keyword